Implementation of Policy Regarding Distribution of BLT for Extreme Poverty in Tambolongan Village, District. Bontosikuyu District. Selayar - Patmawati, Andi Kiki; Mahsyar, Mahsyar; Damirah, Damirah; Muliati, Muliati; Semaun, Syahriyah (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
Policy implementation is any action taken by the government, both individually and in groups, to achieve a goal. Extreme poverty generally means the inability of a community to meet basic needs such as food, drinking water, proper sanitation, health, housing, education and access to information about income and social services. The purpose of this research is the BLT program to help households that are vulnerable to the impact of the Covid-19 pandemic. Qualitative descriptive research method. Primary data comes from direct interviews with direct beneficiaries of extreme poverty in Tambolongan village. The results of this study are: (1) The village government in determining extreme poverty communities still refers to Perkades 01 of 2023 which as been agreed upon with community leaders. (2). Policy implementation carried out by the Tambolongan Village government includes communication, implementing attitudes, bureaucratic structure, and resources. The team involved in the policy of distributing Aid to extreme poverty communities is the implementing team carrying out the Fund Budgeting proposed by the coaching team for evaluation. After that, the Village Fund is ready to be distributed to people of extreme poverty. (3). The concept of economic empowerment for the people guided by the Al-Qur'an lies in the utilization and distribution of wealth evenly which is carried out properly and correctly. There are two provisions recommended in the Al-Qur'an, the first is the command to provide assistance to the poor through infaq, alms and orders to feed the poor (ṭa'am almiskin), apart from being a form of first aid to the poor to maintain their survival, it can also It is understood that this is one way of Islam in empowering poverty